2019
DOI: 10.1002/biof.1599
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates rheumatoid arthritis via activation of SIRT1‐Nrf2 signaling pathway

Abstract: The present study was designed to explore the biological role of resveratrol (RES) in rheumatoid arthritis (RA) and the underlying mechanism. The adjuvant‐induced arthritic rats were administered RES on the 12th day after model establishment, and then arthritis assessment, oxidative stress measurement, histological examination, and immunohistochemical staining were performed. The primary rat fibroblast‐like synoviocytes (FLS) were isolated and treated with RES in vitro and then cell proliferation and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Many previous studies have already revealed the two redox-sensitive proteins closely implicated in the therapeutic effects on diabetic cardiomyopathy [ 21 , 46 , 57 , 58 ]. More importantly, SIRT1 is involved in the regulation and control of oxidative stress that are associated with diverse stimulus, which appears to be exerted by activating Nrf2, indicating that Nrf2 serves as an important downstream target of SIRT1 signaling [ 25 , 26 , 31 , 59 ]. Additionally, novel observations have suggested that BAK inhibits ROS generation in cardiomyocytes via SIRT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have already revealed the two redox-sensitive proteins closely implicated in the therapeutic effects on diabetic cardiomyopathy [ 21 , 46 , 57 , 58 ]. More importantly, SIRT1 is involved in the regulation and control of oxidative stress that are associated with diverse stimulus, which appears to be exerted by activating Nrf2, indicating that Nrf2 serves as an important downstream target of SIRT1 signaling [ 25 , 26 , 31 , 59 ]. Additionally, novel observations have suggested that BAK inhibits ROS generation in cardiomyocytes via SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nuclear factor-erythroid 2-related factor 2 (Nrf2), an important transcription factor that binds to antioxidant-responsive elements (AREs), shows an outstanding performance in attenuating oxidative damage to consolidate the cellular defense system against diabetic cardiomyopathy [ 23 , 24 ]. Numerous studies have also clearly indicated that SIRT1 could manifest its antioxidative effects via the activation of Nrf2 [ 25 , 26 ]. Therefore, it is of great interest to probe whether SIRT1/Nrf2 signaling plays a vital role in the amelioration actions of BAK against diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol exerts an inhibitory effect on the function of thyroxine so that resveratrol supplementation enhances the expression of BAD and inhibits PD-1 to suppress oral cancer cells [62]. By down-regulation of the snail signaling pathway, resveratrol reduces EMT to inhibit the invasion of colon cancer cells [63]. It is worth mentioning that resveratrol activates tumor suppressor Rad9 to induce premature senescence in lung and breast cancer cells [64].…”
Section: Resveratrol In the Treatment Of Cancermentioning
confidence: 99%
“…However, the accumulating data have shown that the major mechanism for the antioxidant activity of resveratrol is related to its effect on the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway. Resveratrol, by activation of the Nrf2 signaling pathway, ameliorates oxidative stress [68] to improve colitis [69], arthritis [63], diabetes [70] and non-alcoholic fatty liver disease [71].…”
Section: Resveratrol In the Treatment Of Cancermentioning
confidence: 99%
“…Resveratrol (trans-3,4,5-Trihydroxystilbene) is a natural polyphenol found in particularly high concentrations in red wine as well as numerous plants, such as grapes, peanuts, and other groundnuts. It has been attracted intense interest for its potentially beneficial effects and the mechanism of action (Robb, et al, 2008;Wang et al, 2019). It exhibits anti-oxidant, anti-inflammatory, anti-aging and anti-tumorigenic effects (Robb et al, 2008;Kim et al, 2018;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%